MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KOLABORASI MURID KELAS III MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING MENGGUNAKAN MEDIA BENTALA VISTA DI SDN KEBUN BUNGA 6 BANJARMASIN - Aisyah; Fathonah, Siti; Saleha Elma, Yasha; Ahmad Fauzi, A'denan; Karim; Zulpah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low levels of critical thinking and collaboration skills among students in the Natural and Social Sciences course in third grade at SDN Kebun Bunga 6 in Banjarmasin. The purpose of this study was to improve students’ critical thinking and collaboration skills through the implementation of the Problem-Based Learning model using the Bentala Vista medium. This study is a Classroom Action Research (CAR) conducted collaboratively over two cycles. The research subjects were 26 third-grade students at SDN Kebun Bunga 6 in Banjarmasin. Data collection techniques included observation, testing, and documentation. Data analysis employed a descriptive-comparative approach, comparing the pre-cycle, Cycle I, and Cycle II.The results showed a significant improvement. In the pre-cycle phase, students’ critical thinking skills were only 26.92%, and their collaboration skills were only 34.62%. After Cycle I interventions, in Session 1, critical thinking skills increased to 53.85%, while collaboration skills rose to 65.38%. Then, in Session 2, critical thinking skills increased to 61.54%, and collaboration skills increased to 73.08%. In Cycle II, Session 1, the mastery of critical thinking skills reached 73.08%, and that of collaboration skills reached 76.92%. Finally, in Cycle II, Session 2, the mastery of critical thinking skills reached 88.46%, and that of collaboration skills reached 96.15%. Thus, it can be concluded that the implementation of the Problem-Based Learning model using the Bentala Vista media successfully improved the critical thinking and collaboration skills of third-grade students at SDN Kebun Bunga 6 in Banjarmasin.